Investigation of protective effects of olanzapine on impaired learning and memory using behavioral tests in a rat model of Alzheimer’s disease - Komaki, Somayeh; Amiri, Parsa; Safari, Samaneh; Abbasi, Ebrahim; Ramezani-Aliakbari, Fatemeh; Golipoor, Mandana; Kourosh-Arami, Masoumeh; Rashno, Masome; Komaki, Alireza (Frontiers in Aging Neuroscience, 2025)
IntroductionEvidence suggests that oxidative stress plays a critical role in the pathogenesis and progression of Alzheimer’s disease (AD). Consequently, antioxidants may mitigate neurotoxicity induced by beta-amyloid (Aβ) and potentially reduce cell death. Previous research has demonstrated that olanzapine (OLZ) possesses antioxidant and neuroprotective properties. In this study, we investigated the protective and therapeutic effects of OLZ on an animal model of AD induced by Aβ using behavioral assessments.MethodsRats were randomly assigned to one of five groups (n = 10 rats per group): a control group, a sham group that received an intracerebrovascular (ICV) injection of phosphate-buffered saline (the solvent for Aβ), an AD group that received an ICV injection of Aβ, an OLZ group that received OLZ via gavage for two months, and an AD + OLZ group that received OLZ for one month before and one month after AD induction.ResultsWe used the Elevated Plus Maze (EPM), Novel Object Recognition Test (NORT), Barnes Maze (BM), Passive Avoidance Test (PAT), and Morris Water Maze (MWM) to assess behavioral performance in the experimental rats. Aβ administration impaired cognition and increased anxiety-like behavior. Treatment with OLZ improved cognitive decline and reduced anxiety-like behavior in Aβ-infused rats.ConclusionOur findings suggest that OLZ can restore cognitive performance and alleviate anxiety-like behavior following Aβ injection. Thus, OLZ may have both preventive and therapeutic potential for AD and could be considered a viable pharmacological option.